Authorship trends in the Journal of Applied Behavior Analysis: An update. Issue 4 (25th May 2020) - Kranak, Michael P.; Falligant, John Michael; Bradtke, Peter; Hausman, Nicole L.; Rooker, Griffin W.
Abstract : The Journal of Applied Behavior Analysis ( JABA ) is considered the flagship journal for the discipline of applied behavior analysis. Thus, popular research topics and other publication trends within JABA reflect the current cultural and scientific contingencies governing the field of behavior analysis. Researchers have previously quantified a number of authorship trends in JABA (and other behavior‐analytic journals) across a number of variables, such as gender identity and sex of author, country of origin, or seniority within the field (Dunlap et al., 1998) to examine demographic and organizational factors associated with successful publication in JABA . These analyses ought to be conducted continuously to monitor trends and detect any potential biases (e.g., sexism). Accordingly, the purpose of the present investigation was to replicate previous research in this area (e.g., Dymond et al., 2000) and provide an update of current publication trends within JABA . Implications for future research and publishing practices are discussed.